GENDER ASPECTS OF THE DENTAL STATUS IN THE ADULT POPULATION OF THE KHARKIV REGION - Slynko, Yu.O.; Sokolova, I.I.; Karpenko, K.I.; Udovychenko, N.M.; Herman, S.I.; Tomilina, T.V.; Skydan, K.V. (World of Medicine and Biology, 2022)
This study is devoted to analysis of the prevalence of small dental defects in the adult population of the Kharkiv region by gender. Orthopantomograms of 1269 patients of both genders, aged 18 to 84 years, were analyzed. The condition of the dentition in women is better than that of men, namely: small dentition defects (DDs) in women were less than by 1.10 times, large ones – less than by 1.16 times, and the DDs absence, conversely, occurred by 1.3 times more frequently than in men, but the established differences were not statistically significant (χ2=8.859, p=0.012). The study performed also showed that women had smaller DDs in the lower and upper jaws, frontal and lateral areas more frequently than men, but there was no statistical difference between the prevalence of small DDs with regard to topographic and quantitative characteristics and the gender (p>0.05).
Keywords: dentition defects; prevalence; gender differences; gender gap